A polymerase chain reaction for detection of Brucella canis in vaginal swabs of naturally infected bitches - Keid, L. B.; Soares, R. M.; Vasconcellos, S. A.; Chiebao, D. P.; Salgado, V. R.; Megid, Jane [UNESP]; Richtzenhain, L. J. (Elsevier B.V., 2007)
A PCR assay for the detection of Brucella canis in canine vaginal swab samples was evaluated, comparing its performance with that of bacterial isolation, serological tests, and a blood PCR assay. One hundred and forty-four female dogs were clinically examined to detect reproductive problems and they were tested by the rapid slide agglutination test, with and without 2-mercaptoethanol (2ME-RSAT and RSAT, respectively). In addition, microbiological culture and PCR were performed on blood and vaginal swab samples. The results of the vaginal swab PCR were compared to those of the other tests using the Kappa coefficient and McNemar test. of the 144 females that were examined, 66 (45.8%) were RSAT positive, 23 (15.9%) were 2ME-RSAT positive, 49 (34.02%) were blood culture positive, 6 (4.1%) were vaginal swab culture positive, 54 (37.5%) were blood PCR positive, 52 (36.2%) were vaginal swab PCR positive, and 50.69% (73/144) were positive by the combined PCR. The PCR was able to detect as few as 3.8 fg of B. canis DNA experimentally diluted in 54 ng of canine DNA, extracted from vaginal swab samples of non-infected bitches. In addition, the PCR assay amplified B. canis genetic sequences from vaginal swab samples containing 1.0 x 10(0) cfu/mL. In conclusion, vaginal swab PCR was a good candidate as a confirmatory test for brucellosis diagnosis in bitches suspected to be infected, especially those negative on blood culture or blood PCR; these animals may be important reservoirs of infection and could complicate attempts to eradicate the disease in confined populations. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: canine brucellosis; vaginal swab; PCR; microbiological culture; rapid slide agglutination test